Driving Lidl´s growth strategy in Portugal through customer loyalty: assessing price in the implementation of a loyalty program - Ferreira, Leonor Tomaz Branco Vieira (2021)
This report is part of the work project “Driving Lidl's Growth Strategy in Portugal through Customer Loyalty”, developed for the Strategic and Marketing Plan field lab. It assesses how Price, a fundamental element of the Marketing Mix, influences the implementation and maintenance of a Loyalty Program for Lidl, a German grocery and food retailer in Portugal. The aim of this paper is to create a strategic approach on how to develop a lucrative Loyalty Program which increases the average spending per ticket of Lidl.